PEMIKIRAN POLITIK IBNU KHALDUN DAN PEMBENTUKAN TEORI SOSIOLOGI POLITIK - Kamaruddin, Kamaruddin (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2016)
This paper will try to illustrate the concepts offered by Ibn Khaldun on State and government, with the main explanations regarding the concept of ashabiyah (group solidarity) and its role on state formation, rise and collapse. According to the Ibnu Khaldun, ashabiyyah is the driving force of the country and  the foundation for the establishment of a state or dynasty . Ashabiyyah have a major role in the expansion of the country after the establishment of the country's foundation. When ashabiyyah is strong , the states can be expanded otherwise if asabiyyah weak , then the area of the states appears relatively limited